Implementasi Metode Iqro’ dalam Meningkatkan Pemahaman Tajwid Santri Putri Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Ahsena Lutfi Afifah; Mustaqim Hasan; Nurul Aslamiyah (Departement of Mathematics Education, 2024)
This exploration intends to figure out how the application, benefits and impediments of the Iqro' technique work on's how understudies might interpret tajwid at the Hidayatul Mubtadiin Islamic Live-in School, Sidoharjo Town, Jati Agung Area, South Lampung Regime. This examination is a subjective exploration, the kind of exploration is elucidating subjective with the exploration subjects being 3 ustadzahs and 3 understudies in the Iqro' class of the Hidayatul Mubtadiin Jati Agung Islamic Life experience School. Information assortment procedures in this examination are through perception, meetings and documentation. The consequences of the exploration show that the utilization of the Iqro' technique comprises of 3 movement meetings, specifically the Initial Stage, the ustadzah and understudies read hadloroh together followed by perusing Surah Alfatihah. Second, conveying material utilizing old style strategies, traditional perusing and tuning in and individual sorogan. Also, the third action is the end stage. The benefit of applying the Iqro' strategy is that understudies can peruse the Al-Qur'an rapidly as a result of the CBSA technique (Dynamic Understudy Learning Technique), and all Iqro' material is adjusted to understudies' capacities from levels beginning from volumes I, II, III, IV, V, VI. The impediment in executing the Iqro technique is that every understudy's capacities are unique in relation to different understudies and understudies need focus during learning.